PECULIARITIES OF SEVERE LIVER GUNSHOT WOUNDS PATHOMORPHOSIS - Khoroshun, E.M.; Makarov, V.V.; Nehoduiko, V.V.; Tertyshnyi, S.V.; Titov, Ye.V.; Ryzhenko, A.P.; Vastyanov, R.S. (World of Medicine and Biology, 2025)
The purpose of the study was to determine the pathomorphological peculiarities of liver gunshot wounds. The study material was liver slices after gunshot shrapnel wounds to the colon (12 studies) from 1 hour to 6 days after the injury. Histological preparations were taken during primary surgical interventions after gunshot wounds of the liver and during repeated interventions. The most common were superficial cracks and subcapsular hemorrhages of various shapes and sizes, which had a variety of colours from light red to dark blue and were located mainly on the anterior part of the diaphragmatic surface and the anterior parts of the visceral surface of the liver. In case of liver ruptures, violations of the integrity of the liver parenchyma to different depths with the formation of a slit-like cavity were determined. The tissue crushing had different degrees of depth and volume - from superficial, with damage to small subcapsular layers of the parenchyma, to deep, with the transformation of entire liver lobes into a shapeless mass, consisting of crushed cells, partially interconnected by remnants of connective tissue. The authors concluded that liver injuries pathomorphological examination shows the following types of injuries: capsule cracks and subcapsular hemorrhages, liver parenchymal ruptures, crushing, hematomas. In traumatic necrosis of the liver parenchyma, the stromal component in the form of portal tracts remains preserved for the first few days. At the edges of hematomas, on the first day after the injury, perifocal areas of necrosis of the liver parenchyma appear, which are caused by the compressive factor of the hematoma itself. In wounds lasting more than 2 days, the zone of necrosis progresses around the hematomas due to ischemic infarctions, which can be explained by thrombus formation in the vessels and the phenomena of hypovolemic shock.
Keywords: gunshot wounds; liver; pathomorphosis; pathogenetic mechanisms; surgical tactics; treatment; rehabilitation